The International Marketing of Travel and Tourism : A Strategic Approach / edited by François Vellas, Lionel Bécherel - Bécherel, Lioneledited
Tourism marketing has long been considered as a branch of traditional marketing. However, in recent years, tourism marketing has gone through fundamental changes: the pursuit of global strategies based on strategic alliances, the breakdown of commercial borders and advances in new technology have all facilitated the commercialization of tourism products. Setting out to examine the changes shaping the international marketing of tourism and travel this book begins by defining the role of national marketing in tourism and describes the strategic marketing process, from analysis and strategy formulation to implementation techniques. It provides the marketing theory for the rest of the text. Part two focuses on specific issues that are currently influencing tourism marketing. It explains how technology is affecting the way tourism firms operate, the impact and influence of environmental awareness, human resource strategy and service quality on tourism marketing.